DL-3-n-butylphthalide alleviates vascular cognitive impairment induced by chronic cerebral hypoperfusion by activating the Akt/Nrf2 signaling pathway in the hippocampus of rats. (13th April 2018) - Qi, Qianqian; Xu, Jing; Lv, Peiyuan; Dong, Yanhong; Liu, Zhijuan; Hu, Ming; Xiao, Yining; Jia, Yanqiu; Jin, Wei; Fan, Mingyue; Zhang, Dandan; Meng, Nan
Highlights: In this study, we examine whether DL-3-n-butylphthalide(NBP) protects vascular cognitive impairment induced by chronic cerebral hypoperfusion by activating the Akt/Nrf2 signaling pathway in the hippocampus of rats. We found that NBP has potential for improving cognitive and morphological impairments and treating vascular dementia. The study showed that NBP reverses downregulation of oxidative stress-related proteins and upregulation of apoptosis-related proteins in hippocampus. We conclude that NBP may have a protective effect against cognitive impairments by activating of the Akt/Nrf2 signaling pathway and inhibiting apoptosis activity. Abstract: Oxidative stress induced by chronic cerebral hypoperfusion (CCH) plays an important role in the pathogenesis of vascular cognitive impairment (VCI). The Akt/Nrf2 signaling pathway is one of the most important antioxidative stress pathways. To explore whether NBP (DL-3-n-butylphthalide) could alleviate VCI induced by CCH via activating the Akt/Nrf2 signaling pathway and modifying the levels of apoptosis-related proteins, adult male Sprague-Dawley rats were subjected to permanent occlusion of bilateral common carotid arteries (BCCAO) and treated either with vehicle or NBP (applied in two doses, 40 mg/kg and 80 mg/kg) while sham operated animals were treated with vehicle. Treatments were administered daily for 28 days. The obtained results indicate that both administrated doses of NBP significantly ameliorated the spatial learning and memory impairments as indicated by the Morris water maze test while Hematoxylin-Eosin staining revealed that morphological defects in the CA1 area of hippocampus were improved. Moreover, NBP reversed the BCCAO-induced downregulation of investigated oxidative stress-related proteins (p-Akt, t-Nrf2, n-Nrf2 and HO-1) along with the upregulation of pro-apoptotic molecule, Bax and reduction of the expression of anti-apoptotic protein, Bcl-2. According to presented results, NBP may have a protective effect against cognitive and morphological impairments induced by CCH via activation of Akt/Nrf2 signaling pathway and inhibition of apoptotic cascade.